Nutrient Characteristics in Relation to Plant Size of a Perennial Grass Under Grazing Exclusion in Degraded Grassland - Liu, Zhiying; Baoyin, Taogetao; Duan, Junjie; Yang, Guofeng; Sun, Juan; Li, Xiliang (Frontiers in Plant Science, 2018)
Identifying the linkages between nutrient properties and plant size is important for reducing uncertainty in understanding the mechanisms of plant phenotypic plasticity. Although the positive effects of grazing exclusion on plant morphological plasticity has been well documented, surprisingly little is known about the relationship of nutrient strategies with plant shoot size after long-term grazing exclusion. We experimentally investigated the impacts of grazing exclusion over time (0, 9, 15, and 35 years) on the relationships of nutrient traits (nutrient concentration, allocation, and stoichiometry) of with morphological plasticity in Leymus chinensis, which is a dominant species in grasslands of Inner Mongolia, China. Our results showed that there was a significantly negative correlation between the degrees of plasticity and stability of various morphological traits. Increases in plant size by 126.41 %, 164.17 %, and 247.47 % were observed with the increase of grazing exclusion time of 9, 15, and 35 years, respectively. Plant size was negatively correlated with nitrogen (N) and phosphorus (P) concentrations, but was positively correlated with carbon (C) concentration. Biomass partitioning and leaf to stem ratios of nutrient concentrations contributed more than 95% of the changes in N, P, and C allocation in L. chinensis leaves and stems induced by grazing exclusions. Nine years’ grazing exclusion rapidly changed the nutrient concentrations (averaged by -34.84%), leaf to stem nutrient allocations (averaged by -86.75%), and ecological stoichiometry (averaged by +46.54%) compared to free-grazing, whereas there was no significant trend of these nutrient traits across the 9, 15, and 35 years’ grazing exclusion in L. chinensis individuals. Our findings suggest that with the increase of the duration of the grazing exclusion, time effects on plant performances gradually weakened both in plant morphological plasticity and nutrient properties. There is a significant negative effect between plant sizes and nutrient traits under long-term grazing exclusion.